2014
DOI: 10.1089/fpd.2014.1768
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ThreeBacillus cereusStrains Involved in a Major Outbreak of Food Poisoning After Consumption of Fermented Black Beans (Douchi) in Yunan, China

Abstract: Three Bacillus cereus strains isolated from an outbreak of food poisoning caused by the consumption of fermented black beans (douchi) containing B. cereus is described. The outbreak involved 139 persons who had nausea, vomiting, and diarrhea. The strains were isolated from vomit and the unprepared douchi. Two of the strains produced the emetic toxin cereulide, as evidenced by polymerase chain reaction analysis for the presence of the nonribosomal synthetase cluster responsible for the synthesis of cereulide an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…A major outbreak of food poisoning caused by the consumption of Douchi containing Bacillus cereus was also reported (Zhou et al . ). How to control the pathogens involved in Douchi fermentation process is the crux to ensure the fermented soybean food safety.…”
Section: Discussionmentioning
confidence: 97%
“…A major outbreak of food poisoning caused by the consumption of Douchi containing Bacillus cereus was also reported (Zhou et al . ). How to control the pathogens involved in Douchi fermentation process is the crux to ensure the fermented soybean food safety.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, these authors found genetic similarity among an isolate obtained from a patient with others from strawberry butter and spinach cream using molecular methods, showing the importance of the use of distinct methodologies to investigate outbreaks. ZHOU et al (2014) reported another foodborne outbreak due to consumption of fermented black beans (Douchi) and showed the capacity of the strain to produce cereulide on temperatures higher than 37ºC, probably allowing toxin production on intestine and food. Although the illness caused by this bacterium is usually mild, sometimes it can cause death.…”
Section: Bacillus Cereus Group: Genetic Aspects Related To Food Safetmentioning
confidence: 99%
“…Indeed, a B. cereus outbreak in China was attributed to fermented black beans ( doichi ), and 92 patients suffered severe nausea and vomiting (Zhou et al . ). When we examined commercial doenjang products manufactured by major companies in Korea, all contained B. cereus at 1·0–3·5 log CFU g −1 (Rhee et al .…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have detected B. cereus in various soybean-based foods, including doenjang, sunsik (mixed grains and vegetable powder) and sufu (Chinese fermented soybeans) (Han et al 2001;Kim et al 2009a;Lee et al 2009). Indeed, a B. cereus outbreak in China was attributed to fermented black beans (doichi), and 92 patients suffered severe nausea and vomiting (Zhou et al 2014). When we examined commercial doenjang products manufactured by major companies in Korea, all contained B. cereus at 1Á0-3Á5 log CFU g À1 (Rhee et al 2011).…”
Section: Introductionmentioning
confidence: 99%